2020
DOI: 10.1111/pai.13247
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for childhood asthma: A systematic review

Abstract: Background The inability to objectively diagnose childhood asthma before age five often results in both under‐treatment and over‐treatment of asthma in preschool children. Prediction tools for estimating a child's risk of developing asthma by school‐age could assist physicians in early asthma care for preschool children. This review aimed to systematically identify and critically appraise studies which either developed novel or updated existing prediction models for predicting school‐age asthma. Methods Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 57 publications
2
85
0
Order By: Relevance
“…[ 7 ] Due to the heterogeneity of asthma, there are differences in the clinical manifestations of children at different ages, which may make it harder to diagnose asthma in children. [ 8 ] Both genetic and environmental factors contribute to inception and evolution of asthma, while genes play a greater role in pediatric asthma than adults. A genome-wide association study (GWAS) found that the genes associated with childhood asthma are almost 3 times that of adults.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Due to the heterogeneity of asthma, there are differences in the clinical manifestations of children at different ages, which may make it harder to diagnose asthma in children. [ 8 ] Both genetic and environmental factors contribute to inception and evolution of asthma, while genes play a greater role in pediatric asthma than adults. A genome-wide association study (GWAS) found that the genes associated with childhood asthma are almost 3 times that of adults.…”
Section: Introductionmentioning
confidence: 99%
“…As correctly noted by Kothalawala et al 1 in their recent review “Prediction models for childhood asthma: A systematic review,” exemplary reviews of such prognostic models are not widely available. We praise the authors for their rigor of review methods used to summarize existing literature on school‐age asthma prediction models.…”
Section: Figurementioning
confidence: 99%
“…As detailed in our inclusion criteria, we only considered studies which offered predictions for children aged ≤5 years on their risk of developing the future outcome of childhood asthma or wheeze persistence at school age (6-13 years old). 2 Following their meta-analysis of externally validated regressionbased models, Owora et al concluded that based on their pooled estimates of sensitivity, specificity and area under the receiver operating curve (AUC), existing models offer poor predictive performance, particularly among clinically relevant ranges of sensitivity and specificity. We are pleased that Owora et al were able to offer quantitative support for our initial inference that existing models offer moderate performance with modest generalizability.…”
Section: Reply To Owora Et Almentioning
confidence: 99%